Fixed point theorems for semi-groups of self maps of semi-metric spaces - G. Jungck (International Journal of Mathematics and Mathematical Sciences)
We use selected semi-groups of self maps of a semi-metric space to obtain fixed point theorems for single maps and for families of mapstheorems which generalize results by Browder, Jachymski, Rhoades and Waiters, and others. A basic tool in our approach is the concept of commuting maps.